2018
DOI: 10.1101/449165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shifting up a gear with iDNA: from mammal detection events to standardized surveys

Abstract: 1. Invertebrate-derived DNA (iDNA), in combination with high throughput sequencing, has been proposed as a cost-efficient and powerful tool to survey vertebrate species. Previous studies, however, have only provided evidence that vertebrates can be detected using iDNA, but have not taken the next step of placing these detection events within a statistical framework that allows for robust biodiversity assessments.2. Here, we compare concurrent iDNA and camera-trap surveys. Leeches were repeatedly collected in c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Comparisons of species detection by traditional survey approaches and eDNA analysis are now numerous in the literature, and mainly focus on what is and what is not detected within and across different methods (Hänfling et al, ; Leempoel et al, ). Yet, there has been growing incorporation of occupancy modelling to estimate the probability of detecting the focal species, in comparison to one other survey method, either for a single species (Lugg et al, ; Tingley et al, ) or multiple species (Abrams et al, ; Valentini et al, ). Simultaneous multi‐method comparisons for multiple species have been lacking and this study directly addresses this for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparisons of species detection by traditional survey approaches and eDNA analysis are now numerous in the literature, and mainly focus on what is and what is not detected within and across different methods (Hänfling et al, ; Leempoel et al, ). Yet, there has been growing incorporation of occupancy modelling to estimate the probability of detecting the focal species, in comparison to one other survey method, either for a single species (Lugg et al, ; Tingley et al, ) or multiple species (Abrams et al, ; Valentini et al, ). Simultaneous multi‐method comparisons for multiple species have been lacking and this study directly addresses this for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…At present, we would recommend the use of eDNA metabarcoding alongside other non‐invasive surveying methods (e.g. camera traps) when monitoring invasive species or species of conservation concern to maximize monitoring efforts (Abrams et al, ; Sales, Kaizer, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data and scripts supporting this manuscript are available from Dryad Digital Repository https://doi.org/10.5061/dryad.4558p38 (Abrams et al., ). We have anonymised both species and station names as it contains sensitive information about endangered and threatened species.…”
Section: Data Accessibilitymentioning
confidence: 99%
“…Abrams et al (2018) found that the leeches' effectiveness was dependent on the species of the leech. Each leech species had specific mammals it fed off of and the preferential feeding lead to brown leeches (Haemadipsa zeylanica) having DNA from less abundant mammal species, while more abundant species within the mammalian community were detected through tiger leeches (Haemadipsa picta; Abrams et al 2018). The host preference directly affects the species found when utilizing iDNA which can limit the mammals detected.…”
Section: Comparative Studiesmentioning
confidence: 99%